MHz Broadline NMR and HRTEM in the Study of Novel Strongly Correlated Electron Materials - Georgios Papavassiliou; D. Argyriou; Nikos Panopoulos; Dimitris Koumoulis; Nikos Boukos; Michael Fardis; Michael Pissas; Hae Jin Kim; Jin-Gyu Kim (Journal of Analytical Science and Technology, 2011)
139La broadline NMR and HRTEM is used in order to unveil the interplay between local Jahn-Teller (JT) lattice distortions and the magnetic structure in the La1-xCaxMnO3 family of manganites. By increasing x, i.e. diluting the JT active Mn3+ ions, a variety of novel phases is observed, with most spectacular the low T solitonic (stripe) spin arrangement for x≥0.5.